Differential expression of α-l-arabinofuranosidase and α-l-arabinofuranosidase/β-d-xylosidase genes during peach growth and ripening - Di Santo, Mariana Carolina (2009)
Arabinose is the major neutral sugar in peach (Prunus persica (L.) Batsch) cell walls and substantial changes in arabinose content take place not only during peach melting, when a rapid-softening-related depolymerizing activity may be expected, but also at the onset of peach ripening. A full-length cDNA clone sequence referred to as PpARF1 (GenBank accession no. DQ486870) was obtained and determined by bioinformatics' analysis to be a peach α-l-arabinofuranosidase homologue. The deduced PpARF1 translation product is 677 amino acids in length while the mature protein has a predicted molecular mass of 71.6 kD and a theoretical pI of 4.94. Semi-quantitative RT-PCR reactions were conducted to evaluate the expression of both PpARF1 and PpARF/XYL (GenBank accession no. AB264280), the latter encoding a putative bifunctional protein displaying both α-l-arabinofuranosidase and β-d-xylosidase activities. In peach fruit, the PpARF1 gene expression was detected at every developmental stage with a maximum during S2 (lag phase of development) and a subsequent decrease towards S4 (maximal fruit size). In contrast, PpARF/XYL transcript levels were relatively high at the end of S1 (fruit set) and at S3-E (beginning of the cell expansion). Substantial increases in PpARF1 mRNA levels were found at the beginning and end of the climacteric rise and also in melting fruit. In contrast, PpARF/XYL transcripts reached a maximum when fruit firmness was 22-26 N, with a slight decline during the melting stage. PpARF/XYL and PpARF1 were expressed differently in three fruit tissue types as well as in other plant tissues. Ethylene is regarded as the main regulator of peach ripening and the accumulation of PpARF/XYL and PpARF1 transcripts is coincident with the autocatalytic ethylene production during ripening. On the hand, other factors may also play a role in PpARF1 and PpARF/XYL expression, since transcripts accumulate at different developmental times and organs even when ethylene biosynthesis is barely detectable.